EVALUASI HIDDEN CURRICULUM DI SMP NEGERI BOJA, KABUPATEN KENDAL - Neni Lestari; Bambang Suteng Sulasmono (Kelola: Jurnal Manajemen Pendidikan, 2015)
This study aimed to evaluate the implementation and impact of Hidden Curriculum, as well as the determinant factors of success and sustainability in SMPN 2 Boja Kendal. This study was an evaluative research using qualitative approach. The data collected by using observation, interviews, and documentation. Data analyzed by collecting and selecting to be deduce. Validity used triangulation data that combined the result of observation, interviews, and documentation. The results of the study were: 1) The activities of hidden curriculum development at SMPN 2 Boja Kendal, namely: flag ceremony, school environmental management, establishing and enforcing discipline, special religious worship, smiles, greetings and courtesies, exemplary, relationship among students and principal, teachers, and staff, school canteen services. 2) The impact of the hidden curriculum development was the changing of school community’s behavior being better, created clean and beautiful school environment, the improvement of public trust to the school toward their kids’ education. Development of the hidden curriculum could establish students good character and an optimal achievement as well as a good school culture. 3) Internal supporting factors including: qualified human resources, the availability of school facilities, school environment was clean and beautiful. External supporting factors occur in the form of endorsement of the parents, school committees and communities in establishing good and virtuous character for the students.